2011
DOI: 10.4028/www.scientific.net/amr.347-353.2587
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Flow Structure of Non-Premixed Swirl Burner Flows Using PIV

Abstract: This paper focuses on investigating the characteristic modes and structures in non-premixed swirling methane/air flames. Using the Particle Image Velocimetry (PIV) technique, the experiment measured the velocity distributions of the swirling flame. Cold flow conditions have been included to provide a picture of the flow field and to demonstrate the modifications induced by combustion. The characteristic lengths, velocity vectors, streamlines, and velocity distributions are presented and discussed. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The length of center recirculation zone l1 is one of important performance evaluation indexes for a swirl burner, which has great significant on fuel–air mixing and combustion stability . Proper length of recirculation zone can not only effectively promote energy, mass and momentum transfer of fuel and air in swirl burner, but also can ensure the proper convective heat transfer in the combustion chamber to improve the burner efficiency.…”
Section: Design Of Structure and Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The length of center recirculation zone l1 is one of important performance evaluation indexes for a swirl burner, which has great significant on fuel–air mixing and combustion stability . Proper length of recirculation zone can not only effectively promote energy, mass and momentum transfer of fuel and air in swirl burner, but also can ensure the proper convective heat transfer in the combustion chamber to improve the burner efficiency.…”
Section: Design Of Structure and Parametersmentioning
confidence: 99%
“…Ge et al . studied the velocity distribution of flame in non‐premixed swirl burner by the technology of particle image velocimetry (PIV), analyzed the velocity vector and streamline distribution of cold flow field, verified and improved the combustion model. It showed that the recirculation zone with complex flow field appeared in the central of burner outlet from the research result which is important to understand the geometry and characteristics of non‐premixed swirl combustion flame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation